THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND STUDENTS ENGLISH ACHIEVEMENTAT X MIA AND IIS OF SMA NEGERI 8 BENGKULU - Novita Sari; Bambang Suwarno; Dedi Sofyan (Journal of English Education and Teaching, 2018)
The aims of this research were to find out the relationship between students’ emotional intelligence scores and their English achievement scores. This research applied a correlational design. The population consisted of the students’ of SMA Negeri 8 Bengkulu while the sample comprised 70 students’. The data were collected from two instruments, namely, a questionnaire to collect the data on students’ emotional intelligence and a teacher’s score list to collect the data on their English achievement. There was a correlation between students’ emotional intelligence scores and their English achievement scores. However, the coefficient of correlation was 0.261 and it was categorized as ‘low’.